1961
DOI: 10.1021/jo01064a632
|View full text |Cite
|
Sign up to set email alerts
|

Notes- Ethers of Bis(1-hydroxyethyl)ferrocene and 1-Hydrobenzylferrocene.

Abstract: NOTES 1671 trichloride (3.76 g., 0.032 mole) in 20 ml. of methylene chloride at -80°. After allowing the mixture to warm, the solvent was removed at the pump. The yellow-orange solid residue was recrystallized from benzene and then from carbon disulfide. Infrared analysis indicated that the compound was triphenylchloromethane. This was confirmed by hydrolyzing a weighed sample in aqueous acetone and titrating the hydrochloric acid liberated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This new ferrocenophane is, to our knowledge, the first example of a chiral enantiomerically pure oxaferrocenophane obtained by asymmetric synthesis (Scheme ). Indeed, some (β-oxatrimethylene)ferrocenes were reported in the literature, but there are no examples of chiral compounds of this kind . The deprotonation of 1,1‘-(β-oxatrimethylene)ferrocene ( 13 ) was tried with n -BuLi/TMEDA, but the ferrocenophane is totally destroyed without detection of substituted compounds in a 2- or 3-position …”
Section: Resultsmentioning
confidence: 99%
“…This new ferrocenophane is, to our knowledge, the first example of a chiral enantiomerically pure oxaferrocenophane obtained by asymmetric synthesis (Scheme ). Indeed, some (β-oxatrimethylene)ferrocenes were reported in the literature, but there are no examples of chiral compounds of this kind . The deprotonation of 1,1‘-(β-oxatrimethylene)ferrocene ( 13 ) was tried with n -BuLi/TMEDA, but the ferrocenophane is totally destroyed without detection of substituted compounds in a 2- or 3-position …”
Section: Resultsmentioning
confidence: 99%
“…This may be because each proteoglycan species varies in its relative carbohydrate/protein content and thus overlaps extensively in the gradient. Other techniques such as zone electrophoresis (Mashburn & Hoffman, 1971;Mayes et al, 1973) also failed to detect some aspects of heterogeneity revealed by other methods such as sequential extraction or gel chromatography, thus emphasizing the importance of the methods chosen to examine this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Together with differences in amino acid composition this suggested that each type of proteoglycan contained different protein cores. Proteoglycans of cartilage are complex heteropolysaccharides in which a large number of chondroitin sulphate and keratan sulphate chains are linked to a polypeptide backbone. A large proportion can be extracted with 4M-guanidinium chloride and have been shown to contain both aggregated and non-aggregated molecules Rosenberg et al, 1970;Tsiganos et al, 1971;Mashburn & Hoffman, 1971). Equilibrium densitygradient centrifugation of the purified proteoglycans from bovine nasal septum in the presence of 4M-guanidinium chloride was shown to dissociate aggregates and separate a protein-rich fraction from the majority of the proteoglycans .…”
mentioning
confidence: 99%
“…The relative mobilities of heparin, chondroitin sulfate A (or C), and hyaluronic acid in electrophoresis by polyacrylamide gels were 1.1 I : I .OO :0.67 (97), which are the same as in free solution electrophoresis (98). Another type of electrophoretic separation was performed by Mashburn and Hoffman (99), who used a continuous-flow electrophoretic flow separator for the separation of heparin, chondroitin sulfate, hyaluronic acid, and protein.…”
Section: Electrophoresis and Chromatography Of Heparinmentioning
confidence: 99%